The Role and Mechanism of microRNA-1224 in Human Cancer - Ma, Mingwei; Li, Jie; Zhang, Zimu; Sun, Juan; Liu, Zhen; Zeng, Ziyang; Ouyang, Siwen; Kang, Weiming (Frontiers in Oncology, 2022)
MicroRNAs (miRNAs) are a type of small endogenous non-coding RNAs composed of 20-22 nucleotides, which can regulate the expression of a gene by targeting 3' untranslated region (3'-UTR) of mRNA. Many studies have reported that miRNAs are involved in the occurrence and progression of human diseases, including malignant tumors. MiR-1224 plays significant roles in different tumors, including tumor proliferation, metastasis, invasion, angiogenesis, biological metabolism, and drug resistance. Mostly, it serves as a tumor suppressor. With accumulating proofs of miR-1224, it can act as a potential bio-indicator in the diagnosis and prognosis of patients with cancer. In this article, we review the characteristics and research progress of miR-1224 and emphasize the regulation and function of miR-1224 in different cancer. Furthermore, we conclude the clinical implications of miR-1224. This review may provide new horizons for deeply understanding the role of miR-1224 as biomarkers and therapeutic targets in human cancer.